Agriculture Technology and Nutritional Improvement in Nepal: A Critical Scrutiny - Sharma, Laxmi (Rural Development Journal, 2025)
The widespread prevalence of nutrient deficiencies and poor nutritional outcomes is a significant concern in developing countries, particularly in Nepal. This article aims to critically examine the relationship between agricultural technology and nutritional improvement in Nepal, with a focus on the challenges, opportunities, interventions, and policies designed to combat malnutrition. Through a review of secondary data, the article identifies gaps and challenges while also highlighting opportunities to leverage agricultural innovations to address malnutrition and enhance rural livelihoods.